(untitled) (Journal of the College of Basic Education, 2026)
characterized by fluctuation between alliance and conflict. Initially, the Hammadid dynasty emerged as a branch of the Zirid rule, as Bologhin ibn Ziri entrusted Hammad ibn Bologhin with governing the central Maghreb, strengthening the Zirid family’s authority. However, Hammad’s ambitions for independence soon strained their relations, especially after the Zirid decline in Ifriqiya following the Hilalian invasion. In 1007 CE (398 AH), Hammad declared independence from the Zirids, founding the Hammadid state and pledging allegiance to the Fatimid caliph, which was a direct challenge to Zirid authority. Al-Mu’izz ibn Badis, the Zirid ruler, launched military campaigns to suppress the Hammadids, but failed due to the strong fortifications of the Hammadid capital and their strategic advantage. The political and military conflict between the two states continued for decades, fueled by external interventions from the Fatimids and Abbasids, and shaped by the rivalry for regional dominance and religious influence. Despite intermittent attempts at reconciliation, relations between the Zirids and Hammadids remained tense, contributing to the weakening of Islamic authority in the central Maghreb in favor of local forces and migrating Arab tribes.